Vegetable research in India - KALLOO, G (The Indian Journal of Agricultural Sciences, 2013)
Vegetable production increased greatly during the last 50 years, making India the second largest vegetable producer(71 million tonnes) in the world. This could be achieved owing to fast increase in infrastructure facilities, manpower andtechnology generation in the field of vegetable science. Though largest number of vegetable crops are grown in India. the research work was carried out only on a few vegetables. A considerable scope exists for export and processing ofvegetables in India which required additiopal production.During the last 5 decades a tremendous progress could be made in development of varieties, breeding for resistanceand heterosis breeding. During the recent past progress has been made in the development of off-season varieties ofradish (Raphanus sativus L.), tomato (Lycopersicon esculentum Mill. nom. cons.), onion (Allium cepa L.) and cabbage(Brassica oleracea L. var capitata L. f). Production technology changed continuously based on the evaluation of newvarieties, chemicals and other inputs. Control measures for disease and pest management were also developed. Thearticle also deals with guidelines and projections for future in the field of vegetables.